Football coaches' development in Brazil: a focus on the content of learning - Alexandre Vinicius Bobato Tozetto; Larissa Rafaela Galatti; Alcides José Scaglia; Tiago Duarte; Michel Milistetd (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIM The aim of the study was to analyze the lifelong content of learning of coaches. METHODS Eight coaches inserted in an Elite Football Club participated. Rappaport Time Line and semi-structured interviews were used to obtain the data. The coaches' learning was organized according to the theory of Lifelong Learning.1-4 RESULTS The coaches presented in their personal experiences, with their families and as athletes, content of learning such as "leadership development" and "formation of values". In professional experiences, such as in academic training, coach assistants and even coaching, they are also reported as essential in obtaining content of learning (general and specific knowledge, training methods, leadership development, self-control). Finally, the reflexive process is considered by most coaches as a potentiator of learning, with interference on the "coach-athlete relationship", "activity adjustment," among other content of learning. CONCLUSION The content learned throughout the life were defined in certain episodes for presenting different meanings in the life of the coaches, in which they related to a new experience according to their biographies. Therefore, the various episodes offer coaches new experiences, in which they can incorporate, reinforce or renew the content about the coaching process and are responsible for the development of the coach.